The role of nutrition and gut microbiome in childhood brain development and behavior - Jiang, Yue; Li, Yuanyuan (Frontiers in Nutrition, 2025)
The intricate relationship between nutrition, the gut microbiome, and brain development has garnered significant attention in recent years, concerning its implications for child behavior and cognitive function. The gut-brain axis mediates this relationship through microbial modulation of inflammation, neuroactive compounds, and blood–brain barrier integrity, particularly during prenatal and early postnatal periods. Healthy dietary patterns such as whole foods, high-fiber foods, and minimally processed foods play a crucial role in shaping the gut microbiota, promoting microbial diversity and overall gut health. As a result, a balanced and diverse microbiome supports healthy brain function and development. Furthermore, disruptions in gut microbiota composition have been linked to various neurodevelopmental disorders in children, including autism spectrum disorder, attention deficit hyperactivity disorder, and anxiety. By integrating findings from animal models, clinical trials, and epidemiological studies, this review summarizes current advances on how early-life nutrition and gut microbiota interaction influence brain development and childhood behaviors. Ultimately, this paper underscores the potential for dietary interventions to promote optimal neurodevelopmental health and address behavioral issues in children.